KINETIKA JUMLAH LIMFOSIT PADA BERBAGAI DERAJAT INFEKSI DENGUE - , RIZKY RAHMA WIJAYANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : DF(Dengue Fever) / DHF(Dengue Hemorrhagic Fever) is an infection disease that most common in tropics and subtropic country. Severity of DHF can occur in to various grade, there are grade I,II,III and IV. Grade of DHF is caused by immune response from our body to against of viral infection. Immune response for viral infection is showed by specific and non specific immune response, but spesific immune response very important and showed by leucocyte and lymphocyte activity. The aim of research : To know the kinetics of lymphocyte count in all various grade of dengue infection. The method of research : Method of research using secondary data from medical record of patient with retrospective study. Data is taking from medical record departement in RSUP Dr.Sardjito Yogyakarta. Inclusions criteria is adult DHF patient and exclusions criteria is DHF patient which is suffer another viral or bacterial infection. The result of study: there is 72 subjects in this research, DF 18 subjects, DHF I 27 subjects, DHF II 22 subjects and 5 for DHF III. The result of absolute lymphocyte, generally patient which suffer DF/DHF have limfopenia. While the percentage of lymphocyte, there is limfositosis relatif in 5 and 6 days of fever. Based on statistical analyze with one way anova, p value of absolute lymphocyte is <0.05 and p value of lymphocyte percentage is >0.05. Conclusion : there is significancy difference amount of lymphocyte absolute and more severe the dengue infection, amount of absolute lymphocyte is decrease.